Bede’s the Poet Caedmon and the Influence of Islam - Dr. Abdul-Jabbar Jassim Mohammad (PROSPECTIVE RESEARCHES, 2023)
Bede is one of the English literary writers whose works show Oriental and Islamic elements. This aspect in Bede's writings has been completely ignored by Western scholars who intentionally deny any Islamic influence not only on Bede but on other Western writers though there is possibility that his writings reveal many Oriental and Islamic thematic analogies. After reading Bede's works we find many irrefutable evidence of his unacknowledged interest in the Islamic and Oriental scientific heritage. The impact of the Orient on Bede's works is apparent and clearly reflected in his poem The Poet Caedmon which is an imitation to the story of Prophet Mohammad (peace upon him) and the descend of Al- Wahi. A brief comparison between the two stories provides us with evidence that the latter story probably was based on the former. This fact is undeniable since the analogies between the two are striking. One of these analogies is that both stories are religious and their main subjects are the revelation of religions: Caedmon's main idea is the appearance of Christianity and its development, while the story of AlWahi is also a religious one and deals with the appearance of Islam and its development. Another obvious analogy is both Prophet Mohammad's (peace be upon him) and Caedmon's religious missions are conveyed through an ordinary person in Caedmon and Al-Wahi in story of Mohammed.